2014
DOI: 10.7897/2277-4343.05236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yoga Practices on Micronutrient Absorption and Physical Fitness in Rural Residential School Children: A Randomized Controlled Trial

Abstract: [Purpose] This study was conducted with a view to find out the effect of yoga practices on micronu-trient absorption in urban residential school children. [Subjects and Methods] The study population comprised 66 urban school children aged 11-15 years staying in a residential school in Pune City, Maharashtra, India. A stratified random sampling method was used to divide the students into experimental and control groups. There were 33 students in experimental group and 33 students in control group. Both experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…37 Objective data collected from school records and academic tests have shown postintervention improvements in student grades 74 and academic performance. 42 Furthermore, physiological and cognitive outcome measures reported in a few studies have found decreased cortisol concentrations 73 and improvements in cognitive planning and execution, 39 micronutrient absorption, flexibility, grip strength, abdominal strength, 70 respiratory muscle strength, 62 heart rate variability, 60 and stress reactivity, as determined by skin conductance responses. 79 This review has focused exclusively on studies assessing student outcomes; however, it is important to note that a handful of studies have evaluated the effects of yoga interventions for classroom teachers.…”
Section: Review Of Research On School-based Yoga Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Objective data collected from school records and academic tests have shown postintervention improvements in student grades 74 and academic performance. 42 Furthermore, physiological and cognitive outcome measures reported in a few studies have found decreased cortisol concentrations 73 and improvements in cognitive planning and execution, 39 micronutrient absorption, flexibility, grip strength, abdominal strength, 70 respiratory muscle strength, 62 heart rate variability, 60 and stress reactivity, as determined by skin conductance responses. 79 This review has focused exclusively on studies assessing student outcomes; however, it is important to note that a handful of studies have evaluated the effects of yoga interventions for classroom teachers.…”
Section: Review Of Research On School-based Yoga Interventionsmentioning
confidence: 99%
“…A total of 47 publications met the search criteria and were analyzed (Table ). Publications of therapeutic clinical trials conducted in a school setting but not included in the analysis included studies of yoga in students with special educational needs or disabilities and/or emotional, behavioral, and learning difficulties, including attention deficits and autism spectrum disorders, visual impairment, asthma, poor coordination, and mental retardation .…”
Section: Review Of Research On School‐based Yoga Interventionsmentioning
confidence: 99%
“…It is surprise to mention that micronutrient absorption has been enhanced even when no external micronutrient supplements were provided to the participants. 20 After a discussion on various parts of ANS and diseases of annavaha srotas, it can be said that sympathetic and parasympathetic activities are major and have involuntary control over digestive and other systems of our body. Whatever the changes in physiology of annavaha srotas occurs by any means it will affect one of these ANS activities.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researches conducted to identify the factors that contributed to academic performance of students in general found that IQ, micro nutrient deficiency, personality, teacher student relationship etc. are a few to name 2 . Daniel Goleman's book-"Emotional Intelligence: why it can matter more than IQ" have thrown a new light into the concept of emotional intelligence and stated that only 20% of a person's success can be attributed to his/her IQ 3 .…”
Section: Introductionmentioning
confidence: 99%